The Implementation of Individualized Learning Programs for Children with Special Needs - Roslina, Nurlina; Nita Priyanti; Leroy Holman Siahaan (UNIB Press, 2026)
Early Childhood Education plays an essential role in supporting children’s overall development, including motor skills, particularly for children with special needs who have diverse developmental characteristics. Differences in developmental pace, language abilities, behavior, and social interaction require adaptive learning approaches that respond to individual needs. This study aims toescribe the implementation of the Individualized Learning Program (Program Pembelajaran Individual/PPI) in improving the fine motor skills of children with special needs at Integrated Islamic Kindergarten (Taman Kanak-Kanak Islam Terpadu/TKIT) Sahabat, East Jakarta. This research employed a qualitative approach using a case study design. The subjects consisted of three children with special needs and two accompanying teachers. Data were collected through observations, in-depth interviews with teachers, the principal, and parents, as well as documentation of the learning program. The findings reveal that the PPI supports the development of children’s fine motor skills through activities such as threading, drawing, and pasting that are adjusted to each child’s developmental level. The use of varied learning media and individualized instructional strategies helps increase children’s motivation, confidence, and engagement in learning. Challenges in implementation include limited facilities and infrastructure and the need for continuous teacher professional development. Collaboration among teachers, parents, and the school supports the successful implementation of the program.